"Blind Test 3" calculations of the performance and wake development behind two in-line and offset model wind turbines. (January 2015) - Krogstad, Per-Åge; Sætran, Lars; Adaramola, Muyiwa Samuel
Abstract: This is a report on the comparison between measurement data and predictions presented at the "Blind Test 3" Workshop organized jointly by Nowitech and Norcowe in Bergen, 10 and 11 December, 2013. A number of researchers were invited to predict the performances and the wake development behind two model wind turbines that have been extensively tested at the Department of Energy and Process Engineering, NTNU. The turbines were arranged in-line, but slightly offset so that the wake of the upstream turbine only interacted with roughly half the area swept by the second rotor. This is a common event in most wind parks and produces flow fields that are both complicated and harmful for the downstream turbine. As expected it turned out to be a difficult flow to predict. Contributions were received from five different groups using a range of methods, from fully resolved Reynolds averaged Computational Fluid Dynamics (CFD) models to Large Eddy Simulations (LES). The range of results was large but the overall trend is that the current methods predict the power generation as well as the thrust force reasonably well. But there is a large uncertainty in the prediction of the turbulence field in the wake. Hence, the LES method consistently performed better than the others. Abstract : Highlights: The paper describes a blind test where participants calculated the performance of two turbines when only given the geometry. The case consists of two in-line and slightly offset turbines three diameters apart. Predictions were obtained from methods ranging from commercial CFD to LES. The scatter in predictions was high. The LES type methods performed consistently best.